The Future of Journalism Artificial Intelligence Facilitates Agenda-Setting for Bacaini.ID in the Kediri Mayoral Election - Danny Kunto Wibisono; Hari Tri Wasono; Irwa Rochimah Zarkasi (ULTIMA Comm, 2025)
The presence of artificial intelligence (AI) machines brings a significant transformation for journalists in collecting extensive data information, extracting patterns, and facilitating content more quickly and efficiently, allowing journalists to focus on in-depth investigations. AI can also be used to create personalized content, which can assist media in agenda-setting and enhance literacy among the audience. This research illustrates this using the Mediated Data Model Of Communication Flow. The approach used is a mixed method, analyzing data sourced from big data applications and AI Intelligence Media Analytics (IMA), as well as Intelligence Social Analytics (ISA), with the topic "Kediri Mayoral Election." The data instrument employs media crawling Intelligence Social Analytics (ISA) with data sourced from four social media platforms, TikTok, Facebook, Twitter, and Instagram, to gather parameters such as hashtags, number of views, interactions, content influence, number of retweets, location, video duration, and engagement during the period from January 1 to November 30, 2024. Monitoring results from the Big Data and AI system Bacaini leads up to the election.ID shows that news traffic and engagement on social media regarding the candidates for Kediri Mayor increased following the agenda-setting reporting...............